Enhanced ABL-inhibitor-induced MAPK-activation in T315I-BCR-ABL-expressing cells: a potential mechanism of altered leukemogenicity - Härtel, Nicolai; Hanfstein, Benjamin; Müller, Martin Christian; Erben, Philipp (Journal of cancer research and clinical oncology, 2012)
Background Targeted treatment of chronic myelogenous leukemia using imatinib has dramatically improved patient outcome. However, residual disease can be detected in the majority of patients treated with imatinib. Compensatory activation of MAP kinases (MAPK1/2) in response to BCR-ABL-inhibitors has been reported as a potential cytokine-dependent resistance mechanism leading to the rescue of leukemic progenitor cells.
Published online: 17 November 2011
Gesehen am 24.04.2018